Software Engineering Approaches for Offshore and Outsourced Development Second International Conference, SEAFOOD 2008, Zurich, Switzerland, July 2-3, 2008, Revised Papers - Berkling, Kay; Joseph, Mathai; Meyer, Bertrand; Nordio, Martin (Lecture Notes in Business Information Processing, 2009)
Majoreconomicupheavalscanhavethesortofe?ectthatSchumpeterforesaw60 yearsagoascreativedestruction.Inscienceandtechnology,equivalentupheavals resultfromeitherscienti?crevolutions(asobservedbyKuhn)ortheintroduction of what Christensen calls disruptive technologies. And in software engineering, there has been no technology more disruptive than outsourcing. That it should so quickly reach maturity and an unparalleled scale is truly remarkable; that it should now be called to demonstrate its sustainability in the current ?nancial turmoil is the challenge that will prove whether and how it will endure. Early signs under even the bleak market conditions of the last 12 months are that it will not only survive, it will ?rmly establish its role across the world of business. Outsourcing throws into sharp focus the entire software engineering life- cle. Topics as diverse as requirements analysis, concurrency and model-checking need to ?nd a composite working partnership in software engineering practice. This con?uence arises from need, not dogma, and the solutions required are those that will have the right e?ect on the associated activities in the world of the application: e.g., reducing the time for a transaction or making the results of a complex analysis available in real-time. While the business of outsourcing continues to be studied, the engineering innovations that make it compelling are constantly changing. It is in this milieu that this series of conferences has placed itself.